2011
DOI: 10.1002/masy.200900101
|View full text |Cite
|
Sign up to set email alerts
|

Bulk Ring Opening Polymerization of L‐Lactide with Calcium methoxide

Abstract: Summary: Bulk ring opening polymerization (ROP) of L-lactide (LA) initiated by calcium methoxide (Ca(OMe) 2 ) was investigated in LA/Ca molar ratio from 100 to 5000 and reaction times up to 3h at 180 8C. Ca(OMe) 2 showed good activity as ROP catalyst, particularly at high catalyst concentration. The polymerization shows a linear relationship between M n and reaction time, typical of a controlled process. The increase of LA/Ca molar ratio decreases the conversion which was maximum (66%) when the polymerization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Kricheldorf and Serra showed that racemization efficiency in bulk polymerization of LA strongly depended on the metal, kind of ligand and obviously on temperature . Additionally, Dias et al indicated that in case of LA polymerization catalyzed with Ca(OMe) 2 , a decrease in the ratio of [LA] 0 /[Ca(OMe) 2 ] 0 caused an increment of racemization efficacy . Moreover, in case of LA polymerization many side reactions, for instance internal and external transesterification or chain transfer could take place .…”
Section: Introductionmentioning
confidence: 99%
“…Kricheldorf and Serra showed that racemization efficiency in bulk polymerization of LA strongly depended on the metal, kind of ligand and obviously on temperature . Additionally, Dias et al indicated that in case of LA polymerization catalyzed with Ca(OMe) 2 , a decrease in the ratio of [LA] 0 /[Ca(OMe) 2 ] 0 caused an increment of racemization efficacy . Moreover, in case of LA polymerization many side reactions, for instance internal and external transesterification or chain transfer could take place .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, as its monomer is synthesized by the human body, PLA is bioabsorbable being an excellent choice for biomedical applications as the controlled drug release. The PGA is also hydrolytically degradable and its degradation products are nontoxic .…”
Section: Introductionmentioning
confidence: 99%
“…The polymers should be free from compounds potentially hazardous to human health. Because small amounts of catalyst will inevitably be trapped in the polymeric material, less toxic, biologically benign polymerization initiators such as organocatalysts6 as well complexes of magnesium,7–9 calcium,9, 10 zinc,8, 9 iron,5 titanium,11 or bismuth12 are receiving growing scientific interest.…”
Section: Introductionmentioning
confidence: 99%